Rheology and dynamics of a solvent segregation driven gel (SeedGel). Issue 2 (13th December 2022) - Xi, Yuyin; Murphy, Ryan P.; Zhang, Qingteng; Zemborain, Aurora; Narayanan, Suresh; Chae, Junsu; Choi, Siyoung Q.; Fluerasu, Andrei; Wiegart, Lutz; Liu, Yun
Abstract : A good correlation among structures, dynamics and rheology is established for SeedGel, which realizes bicontinuous structures that promises applications in a broad range of research fields. Abstract : Bicontinuous structures promise applications in a broad range of research fields, such as energy storage, membrane science, and biomaterials. Kinetically arrested spinodal decomposition is found responsible for stabilizing such structures in different types of materials. A recently developed solvent segregation driven gel (SeedGel) is demonstrated to realize bicontinuous channels thermoreversibly with tunable domain sizes by trapping nanoparticles in a particle domain. As the mechanical properties of SeedGel are very important for its future applications, a model system is characterized by temperature-dependent rheology. The storage modulus shows excellent thermo-reproducibility and interesting temperature dependence with the maximum storage modulus observed at an intermediate temperature range (around 28 °C). SANS measurements are conducted at different temperatures to identify the macroscopic solvent phase separation during the gelation transition, and solvent exchange between solvent and particle domains that is responsible for this behavior. The long-time dynamics of the gel is further studied by X-ray Photon Correlation Spectroscopy (XPCS). The results indicate that particles in the particle domain are in a glassy state and their long-time dynamics are strongly correlated with the temperature dependence of the storage modulus.